STUDI PEWILAYAHAN DALAM RANGKA PENGELOLAAN LAHAN GAMBUT BERKELANJUTAN DI PROVINSI RIAU - Mubekti, Mubekti (Badan Pengkajian dan Penerapan Teknologi, 2011)
A preliminary study of peat sustainable development zoning was conducted in Riau Province. The background of the study explains the potential of peat land and the role of management planning regarding to sustainable development. The analysis of peat area and its distribution is based on the existing data and field survey. Then peat ecological zoning is derived by using land evaluation method. A brief description of peat is presented to clarify peat formation, peat characteristics, peat role, and carbon emission from peat. The results of field observation show that ahuge of peat area has been unwise exploited, especially for palm oil plantation, and industrial forest estate. The total area of peat land in Riau resulting from the analysis is 4.360.740 hectares, where Indragiri Hilir has the largest among districts in the Province. Peat area can be divided into 4 zones based on its depth, namely (1) food crop, horticulture, plantation estate, and industrial forest estate, (2) horticulture, plantation estate, and industrial forest estate, (3) plantation estate, and industrial forest estate, and (4) conservation area. The cultivated land of peat covers 2.667.581 hectares whereas the un-cultivated land covers 1.693.159 hectares